PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI REKTORAT UNIVERSITAS HALU OLEO - Emiyanti, Emiyanti; Putera, Asrip; Nur, Nofal (-)
This study aims (1) to examine the simultaneous influence of work discipline and work motivation on the performance of the Rectorate employee of Halu Oleo University, (2) to examine the effect of work discipline on the performance of the employee of the Rectorate of Halu Oleo University, (3) to examine the effect of work motivation on employee performance. Halu Oleo University Chancellor. The object of this research is the Rectorate Employee of Halu Oleo University who has the status as a Civil Servant. The population of this research is the Rectorate Employees with the status as civil servants, amounting to 80 people, because the population is less than 100 people, the sample of this research is 80 employees of Halu Oleo University Rectorate as respondents. Collecting research data using questionnaires, research data analyzed using Multiple Linear Regression through SPSS 21 software. The results of this study (1) ) Simultaneously Work Discipline and Work Motivation have a positive and significant effect on the Performance of Rectorate Employees at Halu Oleo University, (2) Work Discipline has a positive and significant effect on the performance of the Rectorate Employees of Halu Oleo University, (3) Work motivation has a positive and significant effect on the performance of the Rectorate Employees of Halu Oleo University.Â